Final unification with three gravitational constants associated with nuclear, electromagnetic and gravitational interactions - UV, Satya Seshavatharam; S, Lakshminarayana (International Journal of Advanced Astronomy, 2016)
By introducing two large pseudo gravitational constants assumed to be associated with strong and electromagnetic interactions, we make an attempt to combine the old Abdus Salam’s ‘strong gravity’ concept with ‘Newtonian gravity’ and try to understand the constructional features of nuclei, atoms and neutron stars in a unified approach. From the known elementary atomic and nuclear physical constants, estimated magnitude of the Newtonian gravitational constant is (6.66 to 6.70) x10-11 m3/kg/sec2. Finally, by eliminating the proposed two pseudo gravitational constants, we inter-related the Newtonian gravitational constant, Fermi’s weak coupling constant and Strong coupling constant, in a generalized approach.